KAJIAN MENEJEMEN SPECIAL EVENT GOLDBLATT DALAM ROAD SHOW SANTRI SEHAT oleh PT BIO FARMA - Feliza Zubair; Dara Anjani Shahidah (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2017)
This study aims to describe the stage of the research, design, planning, coordination, andevaluation conducted by Corporate Communication of PT Bio Farma (Persero) at the Roadshow